Paludisme et interprétations sociales du changement climatique à l’ouest du Cameroun - Estelle Kouokam Magne (Territoire en Mouvement, 2012)
Climate change provides opportunities for scientists to interact with the population as a whole. Through their own experience and their life conditions the actors interpret this scientific message on climate change. One of the main domains of interest is health, particularly diseases such as malaria that are usually linked with human ecology. The paper discusses the ways the knowledge on climate change is interpreted locally and put emphasize on the people complains on climate change as a call for state’s responsibility in the protection of its citizens especially in the domain of health. The methodology is based on archives research conducted at the centre of national archives in Cameroon and the archives of Institute of health of armies in France. Moreover, we use in-depth interviews made with users of health centre during a research project on malaria (2005-2006) and recent interviews made in Bafoussam. The paper’s principal hypothesis is that the local knowledge on malaria and climate change is the result of discourses and practices of sensitization and prevention of malaria. The paper addresses three thematic areas : firstly context and methodology, secondly a brief historical perspective of the fight against malaria in Cameroon and thirdly the social interpretations of climate change.